Turbine Spirometers Metrological Support - Sokol, Yevgen I.; Tomashevsky, R. S.; Kolisnyk, K. V. (Institute of Electrical and Electronics Engineers, 2016)
This article deals with the description of the device and principle of the turbine spirometer action. Mathematic model of the rotation of the rotor of the measuring turbine is shown. According to the results of the turbine research the method of determine the coefficients of the conversion function is proposed. In this paper experimental studies of the proposed method are conducted. Research results have shown the adequacy of the description of the transformation function and methods for determining the coefficients.
Keywords: medical equipment; turbine spirometer; metrological control; measurement error